Uptake and effectiveness of the Australian telephone Quitline service in the context of a mass media campaign. (23rd July 2003) - Miller, CL; Wakefield, M; Roberts, L
Abstract : Objectives : Since June 1997, Australia has run its first nationally coordinated mass media anti-smoking campaign, with all States collaborating to offer a standard Quitline service. An overview of the Australian national Quitline service is presented as well as two studies describing (a) the relationship between television advertising and call volume and type, and (b) the quit rates of callers over time. Design : Data on extent of advertising, as measured by weekly television target audience rating points (TARPs), is compared with weekly call volume and disposition. A randomly selected sample of callers was followed up at 3 weeks, 6 months and 12 months to assess caller appraisal and quit rates. Setting : The Australian Quitline service, in the context of a nationally coordinated, major anti tobacco campaign. Results : In a one year period from June 1997, 3.6% of adult Australian smokers called the Quitline. Weekly call volume was strongly related to TARPs and increased further when an advertisement specifically promoting the Quitline was broadcast. Calls involving requests for counselling, as opposed to brief calls to request quit materials, were more likely with lower TARPs. Of the cohort who were smoking at baseline, 28% reported they had quit smoking at a one year follow up and 5% had been quit for an entire year. Conclusions : In the context of a national mass media campaign, this study illustrates that it is possible to bring together differing State based services to provide an accessible, acceptable, and effective quit smoking service.